Third molar maturity index as an efficient tool for prediction of age in a sample Indian population - A retrospective study - Srikant Natarajan; C Sharada; Shweta Yellapurkar; Nidhin Phillip Jose; Nandita Shenoy; Dilip G Naik (Wolters Kluwer Medknow Publications, 2022)
Introduction: The age of 18 years is an important milestone for legal matters, and developmental parameters of teeth are often used for estimation of this age. The aim of this study is to assess the efficiency of third molar maturity index (I3M) in establishing age of 18 years in Dakshina Kannada population. Methods: A total of 700 orthopantomograms were retrieved from the archives of the radiology department of Manipal College of Dental Sciences, Mangalore. The length and the width of the open apex of the mandibular left third molar was assessed using Image J software and the Third molar maturity Index (I3M) was calculated and correlated with the age of the individual. Results: Receiver operating characteristic (ROC) curve analysis showed the Area under curve of 0.94 and 0.96 in females and males, respectively, for prediction of age of 18 years. The cut-off of 0.08 predicted the 18-year cut-off with 97% specificity and 90.2% negative predictive value. The percentage of the accuracy was 80.23% if the I3M was <0.08. Conclusion: The efficiency of the cut-off of 0.08 of I3M has been tested in various population including Kosovar, Peruvian, South Indian, Libyan, Montenegro, Croatian, African (Botswana), Albanian, and Serbian. Our study also shows the efficiency of the same in South Indian Dakshina Kannada population.